Implementasi Teori Belajar Sibernetik Menurut Landa dalam Pendidikan Agama Katolik - Lay, Sergius; Zebua, Putranias; Naibaho, Megawati; Yese, Blasius Superma; Sipahutar, Antonius (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
This study examines the implementation of cybernetic learning theory as proposed by Landa in the context of Catholic Religious Education. Cybernetic learning theory focuses on how individuals process and manage information during the learning process, dividing thinking into two types: structured and systematic thinking, and heuristic, creative thinking. This approach aims to encourage deep and flexible learning, especially in religious education. The research used a qualitative method with a literature review approach, where the author collected and analyzed various theoretical sources, books, and relevant journals to understand the application of cybernetic theory in religious education. The study found that integrating these two types of thinking into the learning process could help students systematically understand theological concepts while encouraging them to creatively apply religious values in their everyday lives. Additionally, this theory could optimize the use of technology and feedback mechanisms to improve learning outcomes. Despite facing some challenges in its implementation, the findings of this study showed that cybernetic theory could provide valuable insights in designing dynamic, reflective, and meaningful learning experiences in Catholic Religious Education.